UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH MENENGAH PERTAMA SWASTA DARUL ULUM KABUPATEN BATANGHARI - Anistianngsih, Anistianngsih; Jamil, Zawaqi Afdal; Shalahuddin, Shalahuddin (Universitas Yudharta Pasuruan, 2024)
This study aims to find out the efforts of school principals in improving teacher performance, explain the inhibiting and supporting factors in efforts to improve teacher performance. This research is qualitative research with a descriptive basis carried out at Darul Ulum Private Junior High School, Batanghari Regency. The data collection technique uses observation techniques, interviews, documentation and field notes. This research produces three things, namely: (1) The principal's efforts to improve teacher performance that have been carried out by the principal are by making good efforts in improving performance, starting from planning before the teaching and learning process is carried out such as conducting a school work program meeting, assigning tasks to teachers according to their abilities, and by supervising teacher performance. In addition, efforts in organizing are carried out to improve teacher performance, such as placing and assigning tasks that are in accordance with the teacher's ability, completing facilities and infrastructure, and the principal makes efforts internally by establishing cooperation or good relations with educators, providing learning opportunities to develop the abilities of educators. (2 Factors that are supporters and hinders in improving teacher performance at SMPs Darul Ulum Batanghari Regency are, educators at SMPs Darul Ulum Batanghari Regency who should each be given one subject but given more than one subject, and there are also still some teachers who teach not in accordance with their educational background, this can be said that SMPs Darul Ulum Batanghari Regency still needs several professional teachers which can help the teaching and learning process, as for the supporting factors in addition to the quality of teachers who want to develop their abilities as well as the establishment of good communication because of the cooperation carried out by educators is also the head of the teacher. Factors that are obstacles or supporters can be implemented and overcome if there is cooperation and is done well. The conclusion of this study is that the principal's efforts to improve performance at the school already exist but are not optimal, because there are still several obstacles including those who should be given one subject each but given more than one subject, and there are also still some teachers who teach not in accordance with their educational background, this can be said that SMPs Darul Ulum Batanghari Regency still needs efforts principals in improving the performance of their teachers